Effectiveness of movement therapy interventions and training modifications for preventing running injuries: A meta-analysis of randomized controlled trials - Kozinc, Z.; Sarabon, N. (Journal of Sports Science & Medicine, 2017)
Runners are at relatively high risk for sustaining an overuse injury. While many risk factors have been documented so far, previous reviews have mostly failed to identify effective interventions to lower injury risk in runners. To review the high-quality evidence on two types of preventive interventions - movement therapy interventions and training-modification interventions, regarding running-related injury prevention. Pubmed (MEDLINE), PEDro and Cochrane Central Register of Controlled Trials databases were searched in April 2017, with no date or language restrictions, using following search terms: running injury prevention, running injury therapy, running injury incidence, running injury exercise and running injury risk. Studies were included if they were a randomized controlled trial or prospective cohort study, investigated the effects of movement therapy or training modification interventions, contained a population of runners or other populations, involved in running (e.g. military recruits), and reported lower extremity injury incidence rates specific to running. In total, 4935 citations were identified, 69 of which were retrieved for full-text evaluation. Seven articles met the inclusion criteria and were included in meta-analysis. Two separate meta-analyses were carried out for both intervention types. First meta-analysis showed no preventive effects of movement therapy interventions, with an overall risk ratio of 0.98 (p = 0.81, I2 = 42 %). The second meta-analysis showed no overall preventive effect of training modifications, with an overall risk ratio of 0.78 (p = 0.35, I2 = 79%). No evidence was found to support the preventive effects of movement therapy or training modification. This may primarily be due to non-optimal intervention designs, such as using inappropriate placebo exercises. Preventive programs may also be more effective when carried out prior to running program onset.